Institutional Research in the Future: Challenges Within Higher Education and the Need for Excellence in Professional Practice. Issue 157 (17th May 2013) - Calderon, Angel; Mathies, Charles
Abstract: The upcoming challenge for higher education institutions (HEIs) globally is how to respond to an increasing variety of societal needs but with fewer public resources and increased accountability demands. In this chapter we draw attention to the central role institutional research (IR) professionals play in positioning HEIs in a competitive and globalized environment, and the need for them to have a well‐developed set of skills (both generic and specialized) to provide and inform the decision‐making process. We conclude by posing some questions to consider for the practice of IR into the future.